Validation of the Turkish Version of the Skin Cancer Quality of Life Impact Tool (SCQOLIT): A Health Related Quality Of Life Questionnaire for Non-Metastatic Melanoma and Non-Melanoma Skin Cancer - Hilayda Karakok; Seher Bostancı; Bengü Nisa Akay; Deniz Caliskan; can ateş; Serdal Kenan Kose (Mattioli1885, 2023)
Introduction: Skin cancer is the third most common type of cancer worldwide that has increased in incidence. Quality of life (QoL) instruments have been developed to measure the efficacy of treatments of  cancers. Objectives: The only validated tool that can be used in both nonmetastatic skin cancer types is the SCQOLIT. This study aimed to validate the Turkish version of the Skin Cancer Quality of Life Impact Tool (SCQOLIT).   Methods: A total of 141 patients diagnosed and treated for skin cancer within the previous 3 months were included.  The tool was translated into Turkish in accordance with International Translation Guidelines. The Dermatology Quality of Life Index that was used for external validation. Patient demographics were recorded. Results: Question 3 had a factor load of 0.372, indicating the inadequacy of this question in predicting QoL, a point that the original study did not mention. The SCQOLIT had external validity, convergent validity and internal consistency (Cronbach alpha=0.863), and test-repeat-test correlation coefficient was 0.824 (95% confidence interval; 0.644 - 0.918). Patients diagnosed with melanoma had poorer QoL scores. High-risk tumor characteristics in nonmelanoma skin cancer and stage of melanoma had no impact on QoL (p=0.235 for basal cell carcinoma, p=1.00 for squamous cell carcinoma, p=0.635 for melanoma).  Conclusions: The Turkish version of the SCQOLIT is validated. Age was shown to have a statistically significant negative correlation with QoL, while Fitzpatrick skin type, gender, risk classification, stage, history of skin cancer, family history of skin cancer and treatment modality had no effect on QoL.